Argumentation in Educational Policy Disputes: Competing Visions of Quality and Equity. Issue 4 (1st October 2016) - Anagnostopoulos, Dorothea; Lingard, Bob; Sellar, Sam
Abstract : Current debates about test-based accountability policies revolve around questions of how to ensure that all students have access to high-quality schools and teachers. Whether and how one can meet this goal depend, in part, on the nature of the arguments that policy proponents and opponents mobilize in these debates. This article examines these arguments, focusing specifically on how policymakers and educators justify and critique prominent test-based accountability policies, the OECD's PISA, and enhanced teacher evaluation. Drawing on pragmatic sociology and our research on these policies, we show how policy proponents mobilize industrial, market, and civic arguments to define both quality and equity as the efficient production of standardized test scores. In contrast, educators more often employ civic and domestic arguments that expand the definition of educational quality, but do not engage issues of educational equity. We explore how educators can mobilize arguments and the news media to expand the definition of educational quality and equity to enrich both our vision of education and our debates about it.